Good water - Nesbitt, John D. (Five Star, a part of Gale Cengage Learning, 2016)
"Tommy Reeves and his pal Red Armstrong make friends with the Mexican people who live near the ranch where they work. Their foreman tells them to stay away from the Mexican girls, but the boys do not heed the warning and are fired. Then they find out that Vinch Cushman, their former employer, is trying to force the Mexican people off their land by damming the creek that supplies their water. When Red goes to sabotage the dam, he is shot dead. Tommy joins the Mexicans in their exodus, but Cushman is not content with just driving them away. They will have to endure his repeated attacks until a final showdown determines the fate of all involved." -- Amazon.com.